2020
DOI: 10.1016/j.eclinm.2019.100248
|View full text |Cite
|
Sign up to set email alerts
|

Association of sulfur amino acid consumption with cardiometabolic risk factors: Cross-sectional findings from NHANES III

Abstract: Background: An average adult American consumes sulfur amino acids (SAA) at levels far above the Estimated Average Requirement (EAR) and recent preclinical data suggest that higher levels of SAA intake may be associated with a variety of aging-related chronic diseases. However, there are little data regarding the relationship between SAA intake and chronic disease risk in humans. The aim of this study was to examine the associations between consumption of SAA and risk factors for cardiometabolic diseases. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 55 publications
(45 reference statements)
3
28
0
Order By: Relevance
“…Specifically, the amino acid, Dehydroalanine, belonging to the Cysteine (Cys) and methionine (Met) metabolism pathway increased ASCVD risk with an odds ratio of 23.204 (95% CI: 4.106, 131.124) per SD increase in the log2 predicted plasma levels, after controlling for age and sex. Some research studies have documented the negative health consequences including elevated risk for cardiovascular diseases with high-intakes of both Met and Cys [39][40][41]. Our findings suggest an indirect association between Dehydroalanine amino acid and ASCVD risk through these genetic variants.…”
Section: Snps Identified Using the Proposed And Existing Methodssupporting
confidence: 49%
“…Specifically, the amino acid, Dehydroalanine, belonging to the Cysteine (Cys) and methionine (Met) metabolism pathway increased ASCVD risk with an odds ratio of 23.204 (95% CI: 4.106, 131.124) per SD increase in the log2 predicted plasma levels, after controlling for age and sex. Some research studies have documented the negative health consequences including elevated risk for cardiovascular diseases with high-intakes of both Met and Cys [39][40][41]. Our findings suggest an indirect association between Dehydroalanine amino acid and ASCVD risk through these genetic variants.…”
Section: Snps Identified Using the Proposed And Existing Methodssupporting
confidence: 49%
“…The current study included individuals aged 18 years or older from a nationally representative sample of NHAN ES III with data on mortality status (n = 19,598). As done by a previous study [32], participants who reported implausible daily energy intake levels (< 800 kcal or > 4200 kcal for men and < 500 kcal or > 3500 kcal for women) (n = 1132) and participants with missing dietary data (n = 2920) were excluded, leaving 15,546 participants in the current analysis for NHANES III participants (Fig. 1).…”
Section: Study Populationmentioning
confidence: 99%
“…In animal models, a soy-based diet may also reduce RAAS activity, decreasing resistance at the afferent arteriole and decreasing proteinuria (46). Finally, plant-based regimens have been shown to reduce cardiovascular risk (47)(48)(49). These data supported a plant-based diet for nephroprotection in healthy individuals as well as in renal patients (41), in particular with mild proteinuria and diabetic nephropathy (50,51).…”
Section: Effect Of the Quality Of Dietary Proteinsmentioning
confidence: 87%